Origins of English feudalism - Brown, R. Allen (Reginald Allen), 1924- author.
1 online resource (iv, 164 pages).
Keywords: Originally published in 1973, Origins of English Feudalism suggests that English feudalism has, for a long time, been the most controversial and thereby the most highly technical aspect of English medieval history. The book contains relevant sources that will be of use to readers and will allow them to study documentary, literary and archaeological sources from the medieval period. The debate over the establishment of feudalism in pre-Conquest England involves not only the question of the presence or absence of fief, but also of knights and cavalry, castles and vassilic commendation. This book will be of interest to academics and the ease of use and careful division of sources, will be of interest to students.